Mutual Coupling Reduction of DRA for MIMO Applications - Al Shalaby, N.; El-Sherbiny, S. G. (Advanced Electromagnetics, 2019)
In this paper, A multiple input Multiple Output (MIMO) antenna using two Square Dielectric Resonators (SDRs) is introduced. The mutual coupling between the two SDRAs is reduced using two different methods; the first method is based on splitting a spiral slot in the ground plane, then filling the slot with dielectric material, "E.=2.2". The second method is based on inserting a copper parasitic element, having the same shape of the splitted Spiral, between the two SDRAs. The effect of replacing the copper parasitic element with Carbon nanotubes (CNTs) parasitic element "SOC12 doped long-MWCNT BP" is also studied. The antenna system is designed to operate at 6 GHz. The analysis and simulations are carried out using finite element method (FEM). The defected ground plane method gives a maximum isolation of l8dB at element spacing of 30mm (0.6λo), whereas the parasitic element method gives a maximum isolation of 42.5dB at the same element spacing.